Stone Concrete: Composition Design and Preparation Technology - Bestuzheva, A. S.; Tsipurskii, I. L.; Gadai, D. V. (Power technology and engineering, 2020)
Amethod for designing a grout for making stone concrete depending on the required behavior of this material within a rockfill dam is described. Laboratory testing of stone concrete allowed us to establish the relationship between its strength and composition. Given strength parameters of stone concrete, the developed algorithm can be used to design a grout mix of cement, sand, mineral powder, and water with relative viscosity and stability such that the mix can be used to grout a rockfill to a required depth, filling well all the voids. The stone-concrete making cycle on the construction site is considered to determine the effectiveness of this type of work.